2021
DOI: 10.3390/jmse9060649
|View full text |Cite
|
Sign up to set email alerts
|

First Report of the Marine Benthic Dinoflagellate Bysmatrum subsalsum from Korean Tidal Pools

Abstract: Dense patches were observed in the tidal pools of the southern area of Korea. To clarify the causative organisms, the cells were collected and their morphological features were examined using light and scanning electron microscopy (SEM). In addition, after establishing strains for the cells the molecular phylogeny was inferred with concatenated small subunit (SSU) and large subunit (LSU) rRNA sequences. The cells were characterized by a nucleus in the hypotheca, strong reticulations in thecal plates, the separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Park et al [5] reported the marine benthic dinoflagellate Bysmatrum subsalsum from Korean Tidal Pools. They identified two ribotypes of B. subsalsum based on molecular phylogeny.…”
Section: Papers Detailsmentioning
confidence: 99%
“…Park et al [5] reported the marine benthic dinoflagellate Bysmatrum subsalsum from Korean Tidal Pools. They identified two ribotypes of B. subsalsum based on molecular phylogeny.…”
Section: Papers Detailsmentioning
confidence: 99%